From microbial proteins to cultivated meat for alternative meat-like products: a review on sustainable fermentation approaches - Fernando Roberto Paz Cedeno; Olumide Joseph Olubiyo; Sungil Ferreira (Journal of Biological Engineering)
Abstract The global demand for protein is rapidly increasing due to population growth and changing dietary preferences, highlighting the need for sustainable alternatives to traditional animal-based proteins. This review explores cultivated meat and microbial alternative proteins, focusing on their potential to meet nutritional needs while mitigating environmental impacts. It also examines the production of cultivated meat as well as various sources of microbial proteins, including mycoproteins, bacterial proteins, and microalgae, highlighting their nutritional profiles, production methods, and commercial applications. This includes an evaluation of the state of commercialization of mycoproteins and the innovative use of agricultural and industrial by-products as substrates for microbial fermentation. The integration of microbial protein production with the bioenergy sector is evaluated as a relevant alternative to attain a synergetic effect between energy and food production systems. Ultimately, this work aims to underscore the importance of microbial proteins in advancing towards a more sustainable protein production system, offering insights into current challenges and future opportunities in the field of fermentation to produce alternative proteins.